Graphene layers fabricated from the Ni/a-SiC bilayer precursor - Nazarov, A.N.; Vasin, A.V.; Gordienko, S.O.; Lytvyn, P.M.; Strelchuk, V.V.; Nikolenko, A.S.; Stubrov, Yu.Yu.; Hirov, A.S.; Rusavsky, A.V.; Popov, V.P.; Lysenko, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
This paper considers a synthesis of graphene flakes on the Ni surface by
vacuum long and nitrogen rapid thermal treatment of the “sandwich” amorphous (a)
SiC/Ni multilayer deposited on silicon wafer by magnetron sputtering technique. The
lateral size of graphene flakes was estimated to be about hundreds of micrometers while
the thickness estimated using Raman scattering varied from one to few layers in case of
vacuum annealing. Rapid thermal annealing (RTA) in nitrogen ambient results in
formation of multilayer graphene with surface covering up to 80%. The graphene layers
synthesized on Ni during CVD process was used as reference samples. Atomic force
microscopy (AFM) is not able to detect graphene flakes in regime of surface topology
examination because of large roughness of Ni surface. Employment of scanning Kelvin
probe force microscopy (SKPFM) demonstrates correlation of the surface potential and
graphene flakes visible in optical microscopy. Using the KPFM method, potential
differences between Ni and graphene were determined.